Electrokinetic removal of radionuclides contained in scintillation liquids absorbed in soil type Phaeozem. (October 2016) - Valdovinos, V.; Monroy-Guzmán, F.; Bustos, E.
Abstract: Control samples of scintillation liquids – Phaeozem soil mixtures were prepared with different scintillation liquids as the support electrolyte, Install Gel ® XF, (Ultima Gold AB™ and Ultima Gold XR™), to construct the polarization curves, and to select the cell potential with the highest mass transfer to remove 24 Na (15 h) and 99m Tc (6 h) as radiotracers from polluted Phaeozem soil. During the electrokinetic treatment (EKT), the removal of radionuclides contained in scintillation liquids absorbed in Phaeozem soil, liquid phase was characterized by Gas Chromatography coupled with a Flame Ionization Detector (GC-FID) and Fourier Transform Infrared Spectrometry (FTIR), solids by FTIR, before and after the application of cell potential. In this sense, the support electrolyte was selected based on the highest current generated (1 mA), as in the case of scintillation liquid 50% Ultima Gold XR™ + 50% Water (1:1), which was used for 6 h in the presence of a mesh and a titanium rod, as anode and cathode, respectively. Finally, the removal percentage accumulated in the liquid phase after the EKT of Phaeozem soil polluted by 99m Tc was 61% close to the anode after 4 h. It was also 61% for 24 Na close to cathode after 2 h, and after 4 h it was 71.8%. Graphical abstract: Highlights: 24 Na (15 h) and 99m Tc (6 h) were removed as radiotracers from polluted Phaeozem soil. 50% Ultima Gold XR™ + 50% Water (1:1) was used as scintillation liquid in EKT. Mesh and a titanium rod as anode and cathode, respectively, were used in the EKT. 99m Tc showed a removal efficiency of 61.0% close to the anode after 4 h of EKT. 24 Na showed a removal efficiency of 71.8% close to the cathode after 4 h of EKT.